Cardiovascular outcomes of early versus delayed coronary intervention in low to intermediate-risk patients with STEMI in Thailand: a randomised trial - Chotechuang, Yotsawee (Heart Asia, 2019)
BACKGROUND: The benefit of an early coronary intervention after streptokinase (SK) therapy in low to intermediate-risk patients with ST-elevation myocardial infarction (STEMI) still remains uncertain. The current study aimed to evaluate the cardiovascular outcomes of early versus delayed coronary intervention in low to intermediate-risk patients with STEMI after successful therapy with SK. METHODS: We randomly assigned low to intermediate Global Registry of Acute Coronary Events risk score to patients with STEMI who had successful treatment with full-dose SK at Lampang Hospital and Maharaj Nakorn Chiang Mai Hospital into early and delayed coronary intervention groups. The primary endpoints were 30-day and 6-month composite cardiovascular outcomes (death, rehospitalised with acute coronary syndrome, rehospitalised with heart failure and stroke). RESULTS: One hundred and sixty-two patients were included in our study. At the 30 days, composite cardiovascular outcomes were 4.9% in the early coronary intervention group and 2.5% in the delayed group (p=0.682). At the 6 months, the composite cardiovascular outcomes were 16.1% in the early group and 6.2% in the delayed group (p=0.054). CONCLUSIONS: The delayed coronary intervention (>24 hours) in low to intermediate STEMI after successful therapy with SK did not increase in short and long-term cardiovascular events compared with an early coronary intervention. TRIAL REGISTRATION NUMBER: NCT02131103.